Menstrual hygiene management practices among girls aged 9 to 17 years in Mathioya Sub-County, Murang’a County: A descriptive study on personal hygiene practices, menstrual management materials, and disposal methods - Nyarenchi, Janet; Amatu, Mary; Mutembei, Josphiine (African Journal of Science, Technology and Social Sciences, 2025)
Menstrual hygiene is an essential component of women's lives, particularly in underdeveloped nations. Nevertheless, numerous women encounter obstacles and hardships within their homes, schools, and workplaces. Girls living in rural areas may have limited knowledge and readiness in relation to menstruation, which can result in challenges and obstacles. More than 50% of teenage females in developing countries demonstrate unacceptable menstrual hygiene behaviors, particularly among those living in rural areas and attending public schools. Limited data exists regarding menstrual hygiene issues among economically disadvantaged adolescent females in Mathioya sub-county, situated in Murang'a County. This study’s objectives were to evaluate the existing personal hygiene habits, the type of menstrual management material utilized, and the disposal techniques employed to improve menstrual hygiene practices and overall well-being among adolescent girls in the region. The study adopted a descriptive cross-sectional design and utilized a stratified random sampling technique. For participation, the study recruited a cohort of 387 adolescent females aged 9 to 17 years. Findings showed that 80% of the girls continuously adhered to appropriate personal hygiene practices by showering regularly, whereas 20% held a divergent viewpoint. Almost all (94%) of the female participants in the study reported changing their menstrual products every 4–6 hours, whereas 6% changed them twice within that time frame, depending on the intensity of their menstrual flow. Majority (98%), utilized soap and water for hand washing whereas 2%, relied solely on water. Eighty-six (86%) of the female participants utilized a cloth, soap, and water to cleanse their genitalia, whereas 14% relied solely on a cloth and water. In addition, 95% of these girls used disposable sanitary pads to efficiently manage their menstrual periods. Because of their poverty, they faced numerous challenges in acquiring these items (89%). Only 92% of the female participants showed a preference for disposable sanitary pads, despite having received information about various menstrual management options. Due to the issue of period poverty, 85% of people have stated that the government and ministry of education should offer complimentary sanitary products to meet their needs. In the end, 97% of participants indicated that the most efficient approach for disposing of menstrual waste was to dispose of it in pit latrines. However, only 10% had the opportunity to use such latrines, and a substantial 83% of those individuals were unaware of the adverse repercussions associated with the inappropriate disposal of menstrual waste. Following the study findings, the research recommends that the State Department of Basic Education in the MOE should include menstrual hygiene management into the National School Health strategy as part of their education strategy, with the goal of enhancing personal hygiene behaviors among girls. The Murang'a county government and school administration should collaborate to offer support in supplying sanitary items and undergarments to adolescent females. Additionally, schools should provide materials for the proper disposal of menstrual waste and explore alternate alternatives to minimize waste.